Wybrane zmiany w podatku VAT a prawo wspólnotowe - Kowalska, Katarzyna (Chosen Changes in Value Added Tax and European Community Law, 2009)
On 7 November 2008 Polish parliament passed a bill concerning the change of the act about value added tax. This article is devoted to one of essential solutions which is bringing the institution of consignment stock and changes in the extent of VAT tax basis. The main purpose of this article is to evaluate aforementioned legislation solutions, especially in compliance with European Community law and to show how much they are friendly to entrepreneurs. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 50-58